Electrostatic interactions drive native‐like aggregation of human alanine:glyoxylate aminostransferase. (1st November 2017) - Dindo, Mirco; Conter, Carolina; Cellini, Barbara
Abstract : Protein aggregate formation is the basis of several misfolding diseases, including those displaying loss‐of‐function pathogenesis. Although aggregation is often attributed to the population of intermediates exposing hydrophobic surfaces, the contribution of electrostatic forces has recently gained attention. Here, we combined computational and in vitro studies to investigate the aggregation process of human peroxisomal alanine:glyoxylate aminotransferase (AGT), a pyridoxal 5′‐phosphate (PLP)‐dependent enzyme involved in glyoxylate detoxification. We demonstrated that AGT is susceptible to electrostatic aggregation due to its peculiar surface charge anisotropy and that PLP binding counteracts the self‐association process. The two polymorphic mutations P11L and I340M exert opposite effects. The P11L substitution enhances the aggregation tendency, probably by increasing surface charge anisotropy, while I340M plays a stabilizing role. In light of these results, we examined the effects of the most common missense mutations leading to primary hyperoxaluria type I (PH1), a rare genetic disorder associated with abnormal calcium oxalate precipitation in the urinary tract. All of them endow AGT with a strong electrostatic aggregation propensity. Moreover, we predicted that pathogenic mutations of surface residues could alter charge distribution, thus inducing aggregation under physiological conditions. A global model describing the AGT aggregation process is provided. Overall, the results indicate that the contribution of electrostatic interactions in determining the fate of proteins and the effect of amino acid substitutions should not be underestimated and provide the basis for the development of new therapeutic strategies for PH1 aimed at increasing AGT stability. Abstract : Alanine:glyoxylate aminotransferase (AGT) is prone to native‐like and misfolding‐based aggregation, mediated by electrostatic and hydrophobic forces, respectively. It is present in humans as two polymorphic forms: AGT‐Ma and AGT‐Mi. The mutations typical of AGT‐Mi oppositely influence the aggregation process, and synergize with pathogenic mutations causing primary hyperoxaluria type I. Pyridoxal 5′‐phosphate, the AGT coenzyme, strongly stabilizes the protein against aggregation.